2009
DOI: 10.1021/jp9063164
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Deformation Behavior of Polyethylene/Montmorillonite Nanocomposites with Strong Interfacial Interaction

Abstract: Deformation behavior of polyethylene/modified montmorillonites with polymerizable surfactant (PE/P-MMT) nanocomposite with strong interfacial interaction was studied by means of morphology observation and X-ray scattering measurements. The orientation of PE chains was accompanied by the orientation of well-dispersed MMT platelets due to the presence of strong interfacial interaction, and both of the orientations were parallel to the deformation direction. The high degree of orientation of MMT platelets and PE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…2000%). The deformation behavior of PE/P-MMTs nanocomposites has been reported in another work by us; 56 it was found that the synchronous improvements in stress and toughness were attributed to the synergistic movement of PE matrix and P-MMTs.…”
supporting
confidence: 61%
“…2000%). The deformation behavior of PE/P-MMTs nanocomposites has been reported in another work by us; 56 it was found that the synchronous improvements in stress and toughness were attributed to the synergistic movement of PE matrix and P-MMTs.…”
supporting
confidence: 61%
“…All reports revealed that low stretching temperature and high annealing or crystallization temperature encouraged the initiation and growth of cavities around the yield point. Furthermore, Ren et al . and Krajenta and Rozanski et al., found that the non‐crystallizable additives permeated into semi‐crystalline polymers (PE and iPP) affected the generation and development of cavities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, since the stiffness of the nanocomposite is reduced slightly and its toughness enhanced, it can be concluded that the active toughening mechanism is mainly crazing. Crazing is a kind of toughening mechanism that increases the toughness and decreases the stiffness, but is not valid for systems showing enhancement in both strength and toughness at the same time . The good dispersion of rubber particles (Fig.…”
Section: Resultsmentioning
confidence: 99%